PEMBUATAN INTELLIGENT LEARNING SYSTEM BERBASIS WEB MENGGUNAKAN LARAVEL DAN PYTHON (STUDI KASUS: SMA NEGERI 2 KARANGANYAR) - Andrea Ramadhan Cahya Aryana (Jurnal Riset Multidisiplin Edukasi, 2026)
Selecting a major track in senior high school represents a pivotal phase deeply intertwined with students' preferences, capabilities, and future academic planning. The instructional process at SMA Negeri 2 Karanganyar currently relies on conventional methods and lacks a direct, continuous learning evaluation mechanism, leading tenth-grade students to encounter difficulty when choosing their academic track for eleventh grade. To address this issue, this study aims to develop a web-based Intelligent Learning System that couples the Laravel framework as the core architecture with Python as a recommendation engine via REST API, automatically generating tailored learning materials and track recommendations (Science/Social Science). The study employs a mixed-methods approach utilizing the Rapid Application Development (RAD) framework. Data were gathered through observation, interviews, literature review, and documentation, while data analysis was executed by combining SWOT analysis with a Content-Based Filtering algorithm powered by TF-IDF and cosine similarity.